The effects of surface stripping ZnO nanorods with argon bombardment - Thierry Maffeis (Nanotechnology, 2015)
ZnO nanorods are used in devices including field effects transistors, piezoelectric transducers, optoelectronics and gas sensors. However, for efficient and reproducible device operation and contact behaviour, surface contaminants must be removed or controlled. Here we use low doses of argon bombardment to remove surface contamination and make reproducible lower resistance contacts. Higher doses strip the surface of the nanorods allowing intrinsic surface measurements through a cross section of the material. Photoluminescence finds that the defect distribution is higher at the near-surface, falling away in to the bulk. Contacts to the n-type defect-rich surface are near-Ohmic, whereas stripping away the surface layers allows more rectifying Schottky contacts to be formed. The ability to select the contact type to ZnO nanorods offers a new way to customize device behaviour.